A Study of Interior Public Space of Samin Community House During the Ruwat Agung Event in Blora (Case Study of Mr. Lasiyo's House) - Nadia Diptya Widyaswati; Rahmanu Widayat (TAMA: Journal of Visual Arts, 2024)
Home is a basic human need. In its development, the house is not only a living space for protection from all kinds of threats, but also has a philosophical meaning. The Samin community's house reflects the identity of a Saminist who maintains the cultural traditions of his ancestors even though times have developed. The development of the times has not made the Samin people lose their culture, especially in terms of building housing, which is also related to traditional events held by the Samin community group in Klopoduwur village. The traditional event in question is Ruwat Agung. This activity was carried out at the house of Mr. Lasiyo and the Samin Klopoduwur community leader. The problem raised is how to describe the public space of Mr. Lasiyo's house and the pendhapa of the Samin community on normal days and during the Ruwat Agung traditional event. The objectives of this research is describe the interior of the public space of Mr. Lasiyo's house during the Ruwat Agung event. The method used in this research is a descriptive qualitative method, qualitative data analysis by comparing existing data in the field with appropriate literature data. The data obtained for this research was obtained from direct observation, interviews, field notes, visual documentation with photos, videos, sketches and written documents. The data that has been obtained is then analyzed using the method proposed by Miles and Huberman which consists of three stages, namely data reduction, data display, and conclusion drawing or verification (conclusion drawing). Based on the research conducted, it will be found that the description of Mr. Lasiyo's house and the pendhapa of the Samin community in the context of the Ruwat Agung traditional event are very related. Keywords: Philosophical, Samin Community, Traditional house